CARBON MONOXIDE CHEMISORPTION- CHARACTERIZATION AND TESTING OF PREPARED NICKEL CATALYSTS FOR AMINATION OF ETHANOL - Achmad Hanafi Setiawan (Research Center for Chemistry - LIPI, 1994)
Three types of nickel metal catalyst supported on silica gel have been prepared using impregnation, ion exchanged sodium hydroxide and ion exchanged ammonia methods, in order to investigate the influence of preparation methods on metal dispersion and their activities for amination of ethanol. All the catalyst samples had a nominal nickel loading of 5 % (w/w). After preparation, the catalysts were activated by a drying stage followed by calcination and reduction. The result of transferring the nickel salt to the support phase has shown that the impregnation method was the most efficient, and the least efficient being the ion exchanged sodium hydroxide method. The results from the carbon monoxide chemisorption studies showed that the nickel is poorly dispersed(2%) in the impregnated sample, and highly dispersed(20%) in the ion exchanged sample prepared by the ammonia method. The dispersion was lower(6%) for the catalyst prepared by the sodium hydroxide method due to the formation of sodium nickel silicates which were difficult to reduce. The amination of ethanol over these catalysts was found to take place at 503 OK with methane being formed as a byproduct. The ion exchanged sample prepared by the ammonia method gave the highest yield(57%) of ethylamine although its specific activity/m2 nickel metal(4 x 10-7) was similar to the sample prepared by the impregnation method. The retained sodium in the ion exchanged sodium hydroxide catalyst poisoned metal sites for ethanol amination.